The Concept of Directed Flow in the Land Order of the Herbal Plant Preservation Center with an Environmental Architecture Approach - Berlin Bardalena, Berlin Bardalena; Azizah, Siti; Hendra, Failasuf Herman (Journal of Applied Sciences, Management and Engineering Technology, 2023)
Abstract. Mojoroto Village, Kediri City has great potential in the field of herbal plant development, namely by utilizing the yard of the house but has not optimized the existing arrangement. Planning and designing a herbal plant preservation center in Mojoroto, Kediri City, is a special land to accommodate various types of herbal plants so that the wider community can get to know and learn how to cultivate, and research well and correctly. The research method in this design is using qualitative methods. While secondary data include literature studies. Heinz Frick's theory with the theme of Environmentally Friendly Architecture is applied to aspects of land order, form and space that include harmony between humans and nature. The selection of environmentally sound architectural themes has an attachment to the surrounding nature. With the concept of macro nature and the concept of micro, directed land flow is applied in the form off a sequential arrangement of space with one another according to its activities. Keywords: Eco-Friendly Architecture, Kediri City, Preservation, Herbal Plants